Retraction: Qian, W., et al. Sanguinarine Inhibits Mono- and Dual-Species Biofilm Formation by Candida albicans and Staphylococcus aureus and Induces Mature Hypha Transition of C. albicans. Pharmacueticals 2020, 13, 13 - Pharmaceuticals Editorial Office (MDPI AG, 2021)
The journal retracts the article [...]